Health Expenditure and Economic growth: An ARDL Approach for the Case of Iran - Mehrara, Mohsen (Journal of Economics and Behavioral Studies, 2011)
This paper examines the relationship between health expenditure and economic growth in Iran for the period 1970-2007, based on the autoregressive distributed lag (ARDL) approach. The study finds a cointegrating relationship among real GDP, health expenditure, capital stock, oil revenues and education, although among them, health spending explains just a small part of the economic growth. The results indicate that while health care expenditures are among the most important factors in the lowering of infant mortality, they do not make a significant marginal contribution to the economic growth in Iran. This findings call for pressing reforms and improved allocation of resources in health sector.